Buy and Selling in the Perspective of Jahiliyah and Islam a Comparison Study a Review of Sharia Economic History - Ahdi Ahdi; Hamdan Firmansyah (International Journal of Nusantara Islam, 2020)
Buying and selling or trading in the term fiqh are called al-Ba'i which, according to etymology, means selling or replacing. The word al-Ba'i in Arabic is sometimes used for the understanding of his opponent, namely the word al-Syira (buy). Thus, the word al-Ba'i means selling, but also means buying. In terminology, buying and selling is an agreement to exchange objects or goods that have a good value between the two parties, one receives objects and the other receives them in accordance with an agreement or provision that has been justified and agreed upon. In the Qur'an, there are many statements that describe the life of the Arabs, including trade problems. Islam is very concerned about the problem of trade in this Arab nation by setting for them what they need. Many of the Prophet's hadith mention the legal issues of buying and selling, monopoly, accounts payable, profits, etc. Jahiliyah Arabs have a market as a center of trade. Usury is one type of economic transaction that is actually carried out and developed in Arab society. In Islam, buying and selling if it contains usury, illicit goods, reduces scales, and by force.